2012
DOI: 10.1186/1475-2875-11-84
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of malaria infection in Butajira area, south-central Ethiopia

Abstract: BackgroundIn 2005, the Ethiopian government launched a massive expansion of the malaria prevention and control programme. The programme was aimed mainly at the reduction of malaria in populations living below 2,000 m above sea level. Global warming has been implicated in the increase in the prevalence of malaria in the highlands. However, there is still a paucity of information on the occurrence of malaria at higher altitudes. The objective of this study was to estimate malaria prevalence in highland areas of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

29
82
9
4

Year Published

2015
2015
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(124 citation statements)
references
References 20 publications
29
82
9
4
Order By: Relevance
“…The present result is consistent with the study conducted among patients attending public health facilities in Maputo City, Mozambique with 15.7% of prevalence [32]; result from Pakistan, Lal Qilla visited to health care center 17.3% [33] and from Hadhramout, Yemen [34] with 18.8%. This result was higher than reports from Kemisie, Ethiopia [35], Butajira, Ethiopia [36], Bangladesh [37], and Eritrea [38] with 5.3%, 0.93%, 3.97% and 2.2% respectively. In contrary, it is less than that reported in Kersa Woreda Jimma 43.8% [39], Hallaba, Ethiopia [40] with 82.8% and Nigeria by 39.5% [41].…”
Section: Discussioncontrasting
confidence: 73%
“…The present result is consistent with the study conducted among patients attending public health facilities in Maputo City, Mozambique with 15.7% of prevalence [32]; result from Pakistan, Lal Qilla visited to health care center 17.3% [33] and from Hadhramout, Yemen [34] with 18.8%. This result was higher than reports from Kemisie, Ethiopia [35], Butajira, Ethiopia [36], Bangladesh [37], and Eritrea [38] with 5.3%, 0.93%, 3.97% and 2.2% respectively. In contrary, it is less than that reported in Kersa Woreda Jimma 43.8% [39], Hallaba, Ethiopia [40] with 82.8% and Nigeria by 39.5% [41].…”
Section: Discussioncontrasting
confidence: 73%
“…Malaria transmission in the region is seasonal due to climatic and altitude factors [12]. Although some parts of the country have no defined rainfall season, in many areas the number of cases reaches a peak after the main rainfall season, which occurs in July-September each year [6].…”
Section: Introductionmentioning
confidence: 99%
“…The reaction mixture was cooled to room temperature and poured into ice-cooled diluted HCl. The solid separated was filtered, washed with ethanol, dried and purified by re-crystallization from chloroform/ethanol mixture (4:1) to yield a deep violet prism (2).…”
Section: Preparation Of 5-(p-tolylamino)-2-hydroxy-3-undecylcyclohexamentioning
confidence: 99%
“…8 It has been reported that embelin possesses wide spectrum of biological activities, such as antibacterial, antitumor, anti-inflammatory, antimalarial and analgesic. [9][10] In the present study embelin (1) isolated from the fruits of E. schimperi and its semi-synthesized aromatic amine derivatives (2)(3)(4) have been evaluated for their in vivo antimalarial activity against mice infected with P. berghei.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation